2021
DOI: 10.1002/col.22694
|View full text |Cite
|
Sign up to set email alerts
|

Preferred white balance for applications using virtual backgrounds

Abstract: Under the current COVID‐19 global pandemic, most of the world is operating online, which has increased the importance of better understanding the perceived color quality of video conference calls. We performed two experiments to evaluate the white balance appearance preference for images simulating a scene from a video conference call where a person is using a virtual background. Due to the dissimilarities of the light sources used for the subject and the background scene, the overall picture may look aestheti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 15 publications
(15 reference statements)
0
1
0
Order By: Relevance
“…In a study examining the preference of the white point under different illuminations, including artificial and natural light, the variation range of the acceptable white point was closely related to the "colors" of natural light sources [6]. Additionally, the authors' previous work on white balance preference for applications using virtual backgrounds showed that preference was based on the virtual background scene content when the foreground model rendering was constant whereas the primary preference focused on the skin tone of the model when rendered under different CCTs [7].…”
Section: Introductionmentioning
confidence: 99%
“…In a study examining the preference of the white point under different illuminations, including artificial and natural light, the variation range of the acceptable white point was closely related to the "colors" of natural light sources [6]. Additionally, the authors' previous work on white balance preference for applications using virtual backgrounds showed that preference was based on the virtual background scene content when the foreground model rendering was constant whereas the primary preference focused on the skin tone of the model when rendered under different CCTs [7].…”
Section: Introductionmentioning
confidence: 99%